Ukraine as a Chessboard for Great Powers. - Storozhko, Anastasiia; Doležal, Tomáš; Cibulková, Petra, 1977-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
The paper tends to analyse Ukrainian crisis and goals of great powers in intervention into the crisis. The purpose of work is to understand what made Ukraine an important geostrategic region in latest years. Thus, paper will use theoretical approaches of famous academics, who analysed Ukraine from the geopolitical perspective – Huntington, Mearsheimer, Brzezinski and Mackinder. Finally paper tends to analyse what theories are applicable to the current Ukrainian Crisis.
Vedoucí práce: Tomáš Doležal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses